STATE REGULATION OF INVESTMENT INSURANCE COMPANIES IN UKRAINE - О. Zaletov (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
In the article the essence of investment insurance company. The role and importance of investment of insurance companies on formation of investment resources in the economy. The essence of the definition of "investment potential of insurance companies" and its relationship with the definition of "financial strength of insurance companies' insurance and potential insurance companies." By analyzing the structure and dynamics of aggregate investment portfolio of insurance organizations of Ukraine in 2008-2015 years defined contribution insurance sector in the formation of investment resources. The problems and prospects of the investment potential of the insurance market of Ukraine. Directions of improvement of state regulation of investment of insurance companies in Ukraine.